Potential of 10% strawberry gel (fragaria x annanassea) as an alternative bleaching agent for extrinsic discoloration of composite resin: an in vitro study - Mariska Juanita; Christine A. Rovani; Indrya K. Mattulada; Maria Tanumihardja (Journal of Dentomaxillofacial Science, 2019)
Objective: The aim of this study was to examine the potential of 10% strawberry gel in reducing extrinsic discoloration of composite resin.Material and Methods: This was a laboratory experimental study using 40 composite resins molded in 8-mm diameter and 2-mm thickness. Samples were soaked in coffee solution for 7 days to obtain discoloration and checked by VITAPAN classicalÂ®shade guideand adobe photoshop CS4 Version 11.0 by CIEL*a*b method. The discolored samples were randomly divided into two groups of 20 samples of each group. Group I was treated with 10% strawberry gel for Â 8 hours every day in 12 consecutive days and Group II as control group was treated with 10%carbamide peroxide in the same way as group 1.The color change was evaluated on day 3, 6, 9, and 12.Results: The results showed a significant change of the color in each group according to Friedman test (p<0,05) while no significant color change difference of Group I when compared to Group II based on the results of Mann-Whitney test. Either 10% strawberry gel or10% carbamid peroxide could not return the composite resins color into the baseline.Conclusion: 10% strawberry gel has similar potency as 10% carbamid peroxide in reducing extrinsic discoloration of composite resin.